Oral Histoplasmosis - A case report and review - Sunu Ramachandran; Anita Balan (Wolters Kluwer Medknow Publications, 2007)
Histoplasmosis, a rare fungal infection results from inhalation of air borne spores of the organism, Histoplasma Capsulatum. Oral lesions are not common, but when present, they are usually associated with the severe disseminated form of histoplasmosis involving multiple sites with various clinical presentations. An unusual presentation of histoplasmosis as an oral ulcer on the buccal mucosa without any systemic manifestation or any immunosuppression is presented here.